PREPOSISI DALAM KISAH PARA RASUL - MANENGAL, FEYBIE FERGIE STEFANIE (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2014)
ABSTRACT This study is an attempt to classify and analyze the preposition in the Book of Acts in terms of forms and meanings. In analyzing the data the writer used Aarts and Aarts and Harman’s theory, and the data were taken from the Acts of the Apostles based on King James Version. The result of this research shows that in the Book of Acts of the Apostles there are several forms and meanings of preposition. The forms are simple preposition and complex preposition. The meanings of preposition refer to the apposition, cause or reason, comparison, concession, condition, degree, description, direction, design, instrument, manner, material, means, measure, objective genetive, partition, place, purpose, quality, respect, source, time, and value. Key words: English Preposition, Forms and Meanings, Acts of the Apostles